Perjanjian Pemborongan Proyek Pembangunan Pagar, Garasi dan Boxculvert pada PT. Mega Nusa Inti Sawit antara Antonius Robinsar dan Askariadi di Kabupaten Indragiri Hulu - Priadi, Okky Elsa; Bachtiar, Maryati; Hendra, Rahmat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
This study will be conducted in Indragiri Hulu on an agreement between Antonius Robinsar and Koprizal as First Party with Askariadi and Berlin Manurung as the Second Party in contracting construction projects fences, garages and boxculvert. This study aims to determine the construction project contracting agreement fences, garages and boxculvert at PT. Mega Nusa Palm Kernel advance of Antonius Robinsar and Askariadi in Indragiri Hulu. And the next goal to determine the rights and obligations under the construction project contracting agreement fences, garages and boxculvert at PT. Mega Nusa Palm Kernel between Antonius Robinsar and Askariadi in KabupatenIndragiri Hulu. The population in this paper are stakeholders in making this agreement between Antonius Robinsar and Askariadi in Indragiri Hulu. Research data collection system using direct interviews with respondents and data analysis using descriptive methods.From these results it can be concluded that the agreement chartering a tie to a job in which the rights and obligations of each party made a pact chartering include also the consequences to be borne by each party when there is a breach of contract or breach of contract , For authors suggest that it is time for providers of goods / services and the goods / services to be able to understand about the agreement chartering to be made so hopefully with the understanding that has been owned by each of these parties, the agreement chartering formed will cover the interests of all parties and in its implementation no disputes.Key words : Construction Project Chartering Agreements, garage and Boxculvert